TITIK KRITIS MANAJEMEN LABA PADA PERUBAHAN TAHAP LIFE CYCLE PERUSAHAAN: ANALISIS MANAJEMEN LABA RIIL DAN MANAJEMEN LABA AKRUAL - Hastuti, Sri (UI Scholars Hub, 2011)
The objective of this study is to examine whether earnings management choices is different in changes of corporate life cycles (growth to mature and mature to stagnant). This earnings management behavior differences were shown by real earnings management and accrual earnings management. The real earnings management was indicated by three proxy such as abnormal CFO, abnormal discretionary expenses, and abnormal production costs, while accrual earnings management was indicated by discretionary accruals. Using manufacturing companies listed in the Indonesia Stock Exchange from year 2000 to 2009, I classify my sample into various life cycle using dividend payout, sales growth, capital expenditure value, and age. The data was collected using purposive sampling method. Total samples were 58 firms. The empirical results indicate firms in growth-mature and mature-stagnant are conducting income increasing. But this research do not find evidence that firms in growth-mature and mature-stagnant choose real earnings management.